Desenvolvimento de acabamento rolled-on em aço inoxidável - Paulo Ernesto Freiheit Cortes (2009)
Different kinds of finishes exist for steels, a new one known Rolled-On (RO) could show with different surfaces patterns, with different roughness and gloss. This work presents the development of the RO finishes in 439 stainless steel with 1,5mm thick. This new finishes will be produced to substitute the grindings finishes. A RO finishes is obtained using a textured roll in temper rolling process. A rolling process transfer roughness aspect in same time, for twice side of the strip. Laboratoryresults indicate that RO finishes show 45% superior oxidation resistance, greater salt spray corrosion resistance with 0,15% NaCl as your similar (grinding finishes) and better drawability in stretching test. RO was development in ArcelorMittal Inox Brasil industrial plant. It has minor leadtime as other similar finishes. This difference allowed increase of market´s offers, protecting company´s marketshare. This new know-how improves the ArcelorMittal´s portfolio and made possible develop others compatibles finishes